Dress sense : emotional and sensory experiences of the body and clothes - Johnson, Donald Clay, 1940-; Foster, Helen Bradley (New York : Berg, 2007)
Introduction, Helen Bradley Foster and Donald Clay Johnson Part I. Historical Perspectives##1. Sight, Sound, and Sentiment in Greek Village Dress, Linda Welters, University of Rhode Island ##2. More than Costume History: Dress in Somali Culture, Heather Marie Akou, Indiana University ##3. Dress, Hungarian Socialism, and Resistance, Katalin Medvedev, University of Minnesota ##4. Clothes Make the Empire: British Dress in India, Donald Clay Johnson, University of Minnesota ##5. African American Enslavement and Escaping in Disguise, Helen Bradley Foster, University of Minnesota Part II. Living Traditions ##6. Indian Madras Plaids as Real India, Sandra Evenson, University of Idaho ##7. The Role of Scents and the Body in Turkey, Marlene Breu, Western Michigan University ##8. Awakening the Senses: the Aesthetics of Moroccan Berber Dress, Cynthia Becker, Boston University ##9. The Power of Touch: Women's Waistbeads in Ghana, Suzanne Gott, Kansas City Art Institute##10. Performing Dress and Adornment in Southeastern Nigeria, Sarah Adams, University of Iowa Part III. Challenging Traditions##11. Women, Migration, and the Experience of Dress, Mary A. Littrell, Colorado State University and Jennifer Paff Ogle, Colorado State University##12. Handmade Textiles: Manufacturing African Authenticity, Victoria L. Rovine, University of Florida##13. Growing Old and Dressing (Dis)Gracefully, Annette Lynch, University of Northern Iowa, M. Elise Radina, Miami University and Marybeth C. Stalp, University of Northern Iowa Part IV. The Future##14. Embodying the Feminine: Male-to-Female cross-Dressing, Jane E. Hegland, South Dakota State University and Nancy Nelson Hodges, University of North Carolina##15. Virtual Sensation: Dress Online, Suzanne Loker, Cornell University and Susan P. Ashdown, Cornell University
Includes bibliographical references and index.
boek
Keywords: Senses and sensation